Capability of mechanical alloying and SPS technique to develop nanostructured high Cr, Al alloyed ODS steels. (November 2014) - García-Rodríguez, N.; Campos, M.; Torralba, J. M.; Berger, M. H.; Bienvenu, Y.
Abstract : Oxide dispersion strengthened (ODS) Fe alloys were produced by mechanical alloying (MA) with the aim of developing a nanostructured powder. The milled powders were consolidated by spark plasma sintering (SPS). Two prealloyed high chromium stainless steels (Fe–14Cr–5Al–3W) and (Fe–20Cr–5Al+3W) with additions of Y2 O3 and Ti powders are densified to evaluate the influence of the powder composition on mechanical properties. The microstructure was characterised by scanning electron microscope (SEM) and electron backscattering diffraction (EBSD) was used to analyse grain orientation, grain boundary geometries and distribution grain size. Transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM) equipped with energy dispersive X-ray spectrometer (EDX) were used to observe the nanostructure of ODS alloys and especially to observe and analyse the nanoprecipitates. Vickers microhardness and tensile tests ( in situ and ex situ ) have been performed on the ODS alloys developed in this work.